2012
DOI: 10.1590/s0100-83582012000400021
|View full text |Cite
|
Sign up to set email alerts
|

S-metolachlor efficacy on the control of Brachiaria decumbens, Digitaria horizontalis, and Panicum maximum in mechanically green harvested sugarcane

Abstract: -The aim of this study was to assess the efficacy of S-metolachlor applied in pre-emergence conditions for the control of Brachiaria decumbens, Digitaria horizontalis, and Panicum maximum in sugar cane mechanically harvested without previous burning of the crop (green harvest) with the crop residue either left or not on the soil surface. The experiments were established in the field according to a randomized complete block design with four repetitions in a 7 x 2 split-plot scheme. In the plots, five herbicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Mesotrione is also labeled for use in the spring as a POST treatment in sugarcane. Although S-metolachlor is labeled for use in sugarcane in other countries, such as Brazil and Australia (Correia et al 2012), it is not so labeled in the United States, and the results of this study suggested that energycane was tolerant to that herbicide. Diuron applied at 13 and 23 rates did not injure energycane at 28 DAT; however, the injury observed at 56 DAT at 23 rate was enough to reduce biomass production (Table 2).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Mesotrione is also labeled for use in the spring as a POST treatment in sugarcane. Although S-metolachlor is labeled for use in sugarcane in other countries, such as Brazil and Australia (Correia et al 2012), it is not so labeled in the United States, and the results of this study suggested that energycane was tolerant to that herbicide. Diuron applied at 13 and 23 rates did not injure energycane at 28 DAT; however, the injury observed at 56 DAT at 23 rate was enough to reduce biomass production (Table 2).…”
Section: Resultsmentioning
confidence: 62%
“…There are several herbicides, including 2,4-D amine, asulam, atrazine, carfentrazone, clomazone, dicamba, diuron, flumioxazin, halosulfuron, hexazinone, mesotrione, metribuzin, pendimethalin, Smetolachlor, and trifloxysulfuron, currently used in conventional sugarcane (Bhullar et al 2012;Correia et al 2012;Dalley and Richard 2008;Judice et al 2006;Richard and Dalley 2006), which can potentially be used in energycane if there is acceptable crop tolerance. Because differential tolerance and sensitivity of other crops, such as corn (Zea mays L.), to herbicides have been reported (Diebold et al 2004;Green 1998;Grey et al 2000;O'Sullivan and Sikkema 2002;Widstrom and Dowler 1995;Williams et al 2005), energycane tolerance to sugarcane herbicides needs to be evaluated to provide potential growers with options for selective weed control if planted hectares increase in the future in the southeast United States.…”
mentioning
confidence: 99%
“…Apresenta eficácia no controle de plantas daninhas (Brachiaria decumbens, Digitaria horizontalis e Panicum maximum) quando aplicado 1440 g ha -1 (Dual Gold, 960 g i.a. L -1 ) sobre 20 t ha -1 de palha proveniente da colheita de cana-de-açúcar (Correia et al, 2012).…”
Section: Introductionunclassified
“…Atrazine and mesotrione components of the premix have been used for several years in sugarcane in the United States, primarily to target broadleaf weeds (Shaner 2014). S-metolachlor has been used in sugarcane in countries such as Brazil and Australia for PRE control of many annual grasses and nutsedges (Correia et al 2012;Ross and Fillols 2017) but not in the United States before registration of the premix. The efficacy and duration of control of annual grasses, particularly fall panicum, in Florida sugarcane provided by S-metolachlor in the premix will depend on its dissipation and persistence in organic and mineral soils under field conditions.…”
Section: Introductionmentioning
confidence: 99%